The Implementation of PDP Framework in Developing Reading Practice Material for the Topic of Tourism and Hospitality - Norhayati, Norhayati; Din, Maaz Ud (ENLIT, 2023)
Reading is a complex process of understanding the main messages from a text. Reading is a receptive skill, where learners do not need to produce language to do it. They receive and understand it. These skills are sometimes known as passive skills. Reading skill competency can be improved by doing a lot of practice. As learners learn in different ways, one theory of learning focuses on the way information is given to learners and refers to visual, auditory and kinesthetic learners. Regarding those theories, so it is believed that in order to support the learners in improving their reading ability, the learners need to use appropriate reading practice materials that are related to their interests. In developing reading practice materials, one of the frameworks that can be applied is PDP (Pre-During-Post). This framework helps ensure students are motivated, engaged, and active before, while, and after in reading a text. This research was focused in developing reading practice materials for students of tourism and hospitality. The research design used in this study is the research and development method. The result of this study is reading practice materials in PDP frameworks that have contents related to tourism and hospitality topics. The learners showed positive improvement in reading ability after they were given some practice with the developed materials.